Effects of Applied Electrical Field on Biochemical Parameters and Erythrocytes of Rats - Demir, H.; Cakir, T.; Karakaya, C.; Cebi Ilhan, A.; Onursal, N.; Gur, A. (Asian Journal of Chemistry, 2010)
The purpose of this study was to determine whether there was any effect of some biochemical parameters and erythrocyte carbonic anhydrase on electrical field stimulation in female rat. The experiments were performed under the animals´ scientific procedures and conform to National Institute of Health guidelines for the use of experimental animals. This study was carried out on female Sprague-Dawley rats (250-270 g). Comparasons were made using student-t tests. A p value less than 0.001 was considered statistically significant. It was demonstrated that alanine aminotransferase, aspartate aminotransferase, amylase and lactate dehydrogenase in serum were significantly affected by this electric field stimulation (p < 0.001 In addition, particularly carbonic anhydrase activity was affected by applied electrical field.